Etnobotánica medicinal como estrategia de aprendizaje de Biología Vegetal, con los estudiantes de tercer semestre de la carrera de Pedagogía en: Química y Biología en el periodo octubre 2021-marzo 2022. - Rovalino Huaraca, Delia Janneth (2023)
To arouse interest in the topic of medicinal ethnobotany in Plant Biology, it expected to use didactic resources that are very useful for virtual education, since teachers must use ICT, which will help obtain interest, and motivation in the speakers. The main objective of this work is to propose a digital strategy of medicinal ethnobotany for learning plant biology with third-semester students of the Pedagogy of Experimental Sciences: Chemistry and Biology career; whose methodology used was non-experimental, descriptive of a bibliographic type, with evaluation instruments used, which was the survey applied to 25 third-semester students. In the results obtained, it evidenced that 96.3% of the students agree that the digital álbum is a resource that will significantly strengthen learning, which expected to arouse interest in acquiring new knowledge. Therefore, it concluded that the digital álbum is an academic support resource that allows gamified participation in students, which is why they consider the use of ICT as a learning strategy for medicinal ethnobotany in Plant Biology, to examine and provide feedback on learning. In addition, they are digital resources of great contribution and that can be related to technology, allowing the provision of synthesized information with a dialogic combination between text and image, from visual education, their reading will be effective, and will be relevant for pedagogical use in classrooms. of classes.